1995
DOI: 10.1016/0735-1097(94)00448-y
|View full text |Cite
|
Sign up to set email alerts
|

Flow capacity of internal mammary artery grafts: Early restriction and later improvement assessed by doppler guide wire

Abstract: Internal mammary artery graft flow early after operation is characterized by a higher rest velocity than that of vein graft flow. This high velocity maintains flow volume at baseline condition in compensation for the smaller diameter. Although flow reserve does not differ significantly between new and old vein grafts, that for internal mammary artery grafts is significantly reduced soon after bypass surgery. This restricted flow capacity improves late postoperatively because of an increase in diameter and a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 17 publications
2
40
0
4
Order By: Relevance
“…The functional behavior of the LITA graft to the left anterior descending artery has already been well described [18,19]. However, few authors explored the velocity and the quantity of the blood flow in composite arterial grafts.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional behavior of the LITA graft to the left anterior descending artery has already been well described [18,19]. However, few authors explored the velocity and the quantity of the blood flow in composite arterial grafts.…”
Section: Commentsmentioning
confidence: 99%
“…Thus, there is no necessity of further handling (for the anastomosis of another graft) of the LITA One disadvantage of the use of composite arterial grafts is the dependence on the LITA for all the blood supply to the revascularized arteries. Thus, the capacity and reserve of the LITA to supply a quantity of blood sufficient for the revascularized area should be questioned [17].The functional behavior of the LITA graft to the left anterior descending artery has already been well described [18,19]. However, few authors explored the velocity and the quantity of the blood flow in composite arterial grafts.…”
mentioning
confidence: 99%
“…13, 14 However, the ITA graft can adapt to the higher flow demands of the relevant myocardial area, thus resulting in an increased graft diameter, usually identifiable within 1 month. [15][16][17][18][19] Many studies on the coronary flow reserve of the ITA graft after pharmacological intervention with adenosine, dipyridamole, papaverine, and nitroglycerin, …”
Section: Physiological and Metabolic Effects Of Grafts In Cabgmentioning
confidence: 99%
“…Internal mammary artery is superior for its long tern patency rates, whereas saphenous vein graft being larger caliber vessel achieves superior flow dynamics in the early post-operative period. 13 Although many studies have demonstrated the long term advantage of using mixed (Left internal Mammary artery + venous conduits) over pure venous conduits in terms of graft patency, a very few studies have compared left ventricular function, the incidence of post-operative complications and the mean duration of hospital stay in both these groups. The present study aimed to compare the above-mentioned parameters in both the groups.…”
Section: Introductionmentioning
confidence: 99%